Development and early results of a comprehensive sexuality education experience in Italian schools: Alice Chinelli. (25th October 2022) - Chinelli, A; Torri, E; Martinelli, D; Farinella, M; Rancilio, L; Galipò, R; Meli, P; Ubbiali, M; Suligoi, B; Tavoschi, L
Abstract: Background: Comprehensive sexuality education (CSE) is an integrated approach to sexual health and wellbeing promotion, especially effective when performed in school settings, but it is not included in Italian school curricula. This study describes the creation and early results of a pilot experience targeting students attending 20 lower secondary schools (LSS) in 4 Italian regions within EduForIST project, funded by the Ministry of Health. Methods: A literature review and a national survey were used to collect guidelines and best practices in the field of sexuality education (SE), along with focus groups and multisectorial expert consultations. The results informed the development of 4 modules of 2 hours each, addressing: changes in adolescence; emotions and relationships; sexual identities and diversity; sexual consent, pregnancy and sexually transmitted infection (STI) prevention, sexual health services. A final session was dedicated to evaluation. Results: The pre-test results referred to 14 classrooms of 5 schools within 2 Regions, for a total of 266 students. A high level of uncertainty was reported, regarding the topics of personal identity development (37, 4%), experiencing intense emotions during adolescence (18, 1%), the definitions of gender identity, sexual orientation and stereotype (42, 1%), STI symptoms (58, 7%) and prevention (43, 4%). The post-test results were available for 153 students. Pre/post analysis showed an increase of correct answers (p<.05) for 12/15 items investigated. A total of 102 students responded to the satisfaction questionnaire, with positive results. Conclusions: Preliminary results revealed knowledge gaps and high levels of uncertainty among LSS students. Early pre/post evaluation suggested that the pilot activity was effective in enhancing knowledge and decreasing uncertainty in all domains. Evidence collected through this study will foster awareness among policy makers on the value and urgency of introducing CSE in Italian school curricula. Key messages: School-based CSE is the most effective way to positively impact on young people's behaviour and attitudes towards sexuality. However, it is not yet included in Italian school curricula. EduForIST pilot activity represents a first step towards the implementation of an evidence-based approach to sexuality education, to be promoted and implemented equally across Italian schools.